The Determinants of Export Performance in Uzbekistan: An ARDL Cointegration Analysis - Abduvalieva Nilufar Maxamadnosir qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Export growth is a critical driver of economic development, particularly for emerging economies. Uzbekistan 's remarkable transformation into a global export offers a captivating case study. This study aims to identify and analyze the key macroeconomic determinants of Uzbekistan 's export performance from 1992 to 2023, moving beyond static models to capture dynamic economic relationships. Utilizing annual time-series data from the World Bank, this research employs the Autoregressive Distributed Lag (ARDL) model and the Bounds Testing approach to cointegration. This methodology robustly handles a mix of stationary and non-stationary variables and distinguishes between short-run dynamics and long-run equilibrium. Gross Domestic Product (GDP) per capita and gross savings exhibit a significant positive impact on exports in both the short and long run. Conversely, the exchange rate has a significant negative impact, consistent with economic theory. The results underscore the importance of sustained economic growth, domestic capital accumulation, and a competitive exchange rate for export-led growth. The study recommends policies focused on enhancing productivity, encouraging domestic savings, and managing exchange rate stability to further improve export sector.